SIAR HINDU MENINGKATKAN RELIGIUSITAS UMAT - Ida Ayu Tary Puspa; I Putu Suyoga Hindhuyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Extension agents have an important role in the broadcast of Hinduism. Armed with rhetoric as an art of speech, an instructor can do religious broadcasting through dharma discourse as part of Sad Dharma. Hindus need to be enlightened to be able to carry out their religious teachings well. To improve religiosity and understanding of the three Hindu religious frameworks. Through religion concerning religious emotions, rites, ritual equipment, Hindus can believe in the teachings of God in Hinduism. Although through a ritual by means of a ceremony called banten, Hindus must be able to uncover the meaning that lies behind it. Carrying out ceremonies as part of the Acara must also pay attention to moral conduct. Thus, both instructors who do Hindu broadcasting especially enlightened people can lean their faith in Hinduism which is adhered to by the teachings in living life as a religious community.Keywords: Hindu broadcast, religiosity